2 ARYLOXYMETHYL THIAZOLINES AND PENTHIAZO LINES - SCHOLZC, R; DJERASSI, CARL (CIBA PHARMACEUTICAL PRODUCTS, RESEARCH DEPARTMENT DIVISION OF CHEMISTRY, SUMMIT, NJ, EUA, 1951)
A series of 2-(aryloxymethyl)thiazolines and penthiazolines have been synthesized by (A) fusion of the appropriate thioamide with a bromoalkylamine hydrobromide or (B) reaction of a bromoalkyl aryloxyacetamide with phosphorus pentasulfide.
J REPROD FERTIL
Keywords: 2 ARYLOXYMETHYL THIAZOLINES, PENTHIAZO LINES; QUIMICA; QUIMICA ORGANICA; RADICALES LIBRES